2008
DOI: 10.1128/jb.00270-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Protein Machinery Required for Transport of Lipopolysaccharide to the Outer Membrane of Escherichia coli

Abstract: The cell envelope of gram-negative bacteria consists of an inner (IM) and an outer membrane (OM) separated by an aqueous compartment, the periplasm, which contains the peptidoglycan layer. The OM is an asymmetric bilayer, with phospholipids in the inner leaflet and lipopolysaccharides (LPS) facing outward (29, 32). The OM is an effective permeability barrier that protects the cells from toxic compounds, such as antibiotics and detergents, thus allowing bacteria to inhabit several different and often hostile en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
292
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(309 citation statements)
references
References 41 publications
17
292
0
Order By: Relevance
“…To determine whether the defect in LptD biogenesis is specific to the loss of LptE, we analyzed cells depleted for different Lpt factors, because depletion of any Lpt factor results in the same lethal envelope defects that could indirectly compromise disulfide bond formation (26,38). An LptF/G double depletion strain (39) revealed that depletion of LptFG does not result in defective oxidation of LptD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the defect in LptD biogenesis is specific to the loss of LptE, we analyzed cells depleted for different Lpt factors, because depletion of any Lpt factor results in the same lethal envelope defects that could indirectly compromise disulfide bond formation (26,38). An LptF/G double depletion strain (39) revealed that depletion of LptFG does not result in defective oxidation of LptD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LptE is anchored to the inner leaflet of the OM via an N-terminal lipid moiety. To understand the role of this lipid anchor in bringing the LptD/E complex together in vivo, we engineered a plasmid in which the coding sequencing of LptE, excluding its signal sequence and the N-terminal lipidated cysteine (a.a. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], is placed after the sequence encoding the pelB leader peptide. This plasmid constitutively expresses a soluble version of LptE in the periplasm that is no longer lipidated at the N terminus.…”
Section: Resultsmentioning
confidence: 99%
“…1). Current models propose that another ABC transporter consisting of LptB, LptC, LptF, and LptG (formerly YhbG, YrbK, YjgP, and YjgQ, respectively) extracts LPS from the IM, initiating the transport and assembly of LPS to its final destination (9)(10)(11)(12). Because LPS is amphipathic, it is unlikely to diffuse across the periplasm unassisted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of the transporter ABC, LptBFG and LptA and LptC translocate the LPS to the internal side of the external membrane such that the proteins LptD and LptE place it on the surface of the membrane. It has been observed an absence of LptA or LptB or both causes the accumulation of LPS in the periplasm [11][12][13][14][15][16][17].…”
Section: Lps and Its Transportation To The External Membranementioning
confidence: 99%